Bioflocculant from pre-treated sludge and its applications in sludge dewatering and swine wastewater pretreatment. (November 2015) - Guo, Junyuan; Ma, Jing
Highlights: A bioflocculant was produced by using alkaline-thermal (ALT) pre-treated sludge. Sludge dewatering by this bioflocculant was discussed compared with chemicals. The application of this bioflocculant in real wastewater treatment was investigated. Flocculating mechanisms were detected by using kaolin suspension in present of Ca 2+ . Abstract: Potentials of alkaline-thermal (ALT) pre-treated sludge as a bioflocculant were studied in sludge dewatering and swine wastewater pretreatment. When incubated with this ALT pre-treated sludge, dry solids (DS) and specific resistance to filtration (SRF) of typical wastewater activated sludge reached 22.5% and 3.4 × 10 12  m/kg, respectively, which were much better than that obtained with conventional chemical flocculants. Sludge dewatering was further improved when both the bioflocculant and conventional polyaluminum chloride (PAC) were used simultaneously. Charge neutralization and inter-particle bridging were proposed as the reasons for the enhanced performance in the case of the combined use. With swine wastewater, the bioflocculant could remove COD, ammonium and turbidity by 45.2%, 41.8% and 74.6% when incubated with 20 mg/L at pH 8.0. This study suggested that the ALT pre-treated sludge has a great potential as an alternative bioflocculant to conventional flocculants in sludge dewatering and swine wastewater pretreatment.